Understanding participants’ experiences of a behaviour change intervention within cardiac rehabilitation: A nested process evaluation within the STRENGTH randomised controlled trial - Clare T. M. Doherty; Mark A. Tully; Jason J. Wilson; Victoria Irving; Lisa Spratt; Rachel O’Reilly; Kim Kensett; Nicole E. Blackburn (PLoS ONE, 2026)
Background The STRENGTH (Self-management and Theory-based Rehabilitation Encouraging New Gateways to Healthy-Hearts) study evaluated a behaviour change intervention embedded within cardiac rehabilitation for individuals with coronary heart disease. This manuscript reports the process evaluation, which aimed to explore participants’ experiences of physical activity, barriers and facilitators to maintaining physical activity, and contextual and process-related factors influencing engagement with the intervention. Methods A process evaluation was nested within a two-arm cluster randomised controlled trial. Semi-structured interviews were conducted with participants from both intervention and control groups, focus groups were conducted with intervention participants. Thematic analysis examined factors influencing physical activity maintenance, including context, implementation, mechanisms of impact and perceived outcomes. Quantitative procedures measured intervention fidelity through attendance records and participant diaries. Results Both groups highlighted environmental, social, and personal factors influencing participation in cardiac rehabilitation, such as social support, professional oversight, and structured programming. Trainers and peer interactions were valued for motivation and perceived safety. The intervention group reported additional facilitators, including tailored support, external accountability, and self-monitoring, which increased awareness and reinforced adherence. Mechanisms of impact included increased awareness of physical activity, greater exercise confidence, and a sense of accomplishment. A perceived lack of exercise confidence may have hindered independent physical activity engagement. Conclusions While behaviour change strategies can enhance engagement in cardiac rehabilitation, their impact on measurable health outcomes remains unclear. Social support, professional oversight, and structured programming appear effective in maintaining physical activity levels, but future interventions should prioritise exercise confidence and education to promote sustained behaviour change. Trial registration Registered with ClinicalTrials.gov on 26-01-2023 (ID: NCT05705310 ).